1996
DOI: 10.1128/jcm.34.4.977-979.1996
|View full text |Cite
|
Sign up to set email alerts
|

Indications of in vivo transfer of an epidemic R plasmid from Salmonella enteritidis to Escherichia coli of the normal human gut flora

Abstract: The presence of conjugative R plasmids as well as the possible similarities among them were studied in nine ampicillin-resistant Salmonella enteritidis isolates and nine ampicillin-resistant Escherichia coli isolates from the normal fecal flora that were simultaneously isolated from nine epidemiologically unrelated outpatients. It was found that in eight patients, ampicillin resistance in S. enteritidis was encoded by ca. 34-MDa transferable plasmids very similar to those found in a recent study of the epidemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
15
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(17 citation statements)
references
References 24 publications
2
15
0
Order By: Relevance
“…The most numerous coliform bacillus in human isolates, E. coli, would be a good candidate for this. We have already shown that E. coli of the normal human faecal flora can harbor the same 34-MDa R plasmid as S. enteritidis simultaneously isolated from the same sample [26]. This is consistent with the hypothesis of in vivo transfer of resistance genes among Salmonella spp.…”
Section: Discussionsupporting
confidence: 88%
“…The most numerous coliform bacillus in human isolates, E. coli, would be a good candidate for this. We have already shown that E. coli of the normal human faecal flora can harbor the same 34-MDa R plasmid as S. enteritidis simultaneously isolated from the same sample [26]. This is consistent with the hypothesis of in vivo transfer of resistance genes among Salmonella spp.…”
Section: Discussionsupporting
confidence: 88%
“…Some studies have investigated the transfer of antibiotic resistance genes (9,(36)(37)(38)(39) both across species and within them, but little has been reported on the transfer of key virulence factors, such as toxins. The possibility that plasmid transfer can occur inside animals has been considered since the 1960s and has been shown in a variety of models, mostly under antibiotic selective pressure (8,10,40,41). This study demonstrated that both the virulence and antibiotic resistance-encoding plasmids of necrotic enteritis-associated C. perfringens are conjugative within the chicken gastrointestinal tract, without selection.…”
Section: Ber-ne33 Ber-ne33/pnetb Pbd1 Pbd1/pnetb Ehe-ne18 Wer-ne36 Bementioning
confidence: 73%
“…However, there is a high degree of rapid plasmid-mediated transfer of CTX resistance between fecal E. coli and Salmonella, as well as other Enterobacteriaceae, and thus, commensal E. coli can be used as a reasonable surrogate to measure the development of resistance in bacterial enteric pathogens. [37][38][39] We have shown that daily CTX did not result in increased P. falciparum antifolate resistance; rather, daily CTX was associated with a reduced incidence of malaria and antifolateresistant genotypes compared with HIV-infected individuals not taking daily CTX. In contrast, daily CTX increased carriage of non-susceptible pneumococci and CTX-resistant E. coli and may accelerate the development of CTX resistance among respiratory and diarrheal pathogens, especially in areas with lower baseline CTX resistance.…”
Section: Discussionmentioning
confidence: 99%